DECISION MAKING AND MANAGEMENT BY OBJECTIVES IN PERUVIAN COMPANY - Begazo Villanueva, José Domingo (2014)
Since we are in a society where knowledge is commoditized, making decisions only being the process through which a need for a decision is identified, it is not sufficient to establish alternatives, analyze them and choose one of them, and implement it to finally assess the results. Should be supplemented with a management by objectives that constitutes a form of conduct and organization of the government to base its conception in anticipating and preparing early achievements and the demarcation and allocation of responsibilities. So that decision making is a tool to make the best decisions on behalf of the company, affecting management, identifying the objectives that will lead to achieving competitive advantage and market success. The problem of this research focuses on the correlation of the decision-making and management by objectives in the Peruvian company; looking to strengthen political commitment and accountability for results that complements the paradigm of management rules and procedures prevailing in the dosage forms of the Peruvian company.